Development of an enclosed-impeller ventricular assist device using self-bearing motor - Zhang, Dongsheng (2009)
Congestive heart disease is currently a major killer. Hence, there is an increasing need for implantable artificial hearts as an alternative to donor hearts which cannot meet the needs. The development of magnetically suspended Ventricular Assist Devices (VADs), alias blood pumps, has been a promising option for this purpose in recent years. In order to overcome the limitations of the current axial flow blood pump available, such as low motoring and pump efficiencies as well as large size, an axial-flow blood pump featuring an enclosed-impeller and self-bearing motors is proposed in this thesis. Computational fluid dynamics (CFD) analysis is carried out to analyze the pump characteristics of the proposed blood pump. The results show that the proposed blood pump could provide 50 mmHg pressure head with 26% pump efficiency at the operating point of 9,000 rpm rotating speed at 5 L/min flow rate. The maximum blood shear stress and maximum blood exposure time is 200 Pa and 146 ms respectively, which indicates lower blood trauma tendency in the proposed blood pump. A prototyped Lorentz force type self-bearing motor test rig is designed with the aid of finite element analysis (FEA) to validate the control scheme for the proposed self-bearing motor. The self-bearing motor is successful levitated by a Proportional-Integral-Derivative (PID) control scheme with a maximum displacement deviation of 0.3 mm. The maximum deviation is further reduced to 0.21 mm by the proposed PID-Robust Model Reference Adaptive Control (RMRAC). The stability control of the proposed PID-RMRAC under output disturbance is also verified through the experiments. These experimental results indicate that the proposed blood pump could be a better alterative for the future development of blood pumps.